ATG Ubiquitination Is Required for Circumsporozoite Protein to Subvert Host Innate Immunity Against Rodent Malaria Liver Stage - Hong Zheng; Hong Zheng; Hong Zheng; Xiao Lu; Xiao Lu; Kai Li; Feng Zhu; Chenhao Zhao; Taiping Liu; Yan Ding; Yong Fu; Kun Zhang; et al. (Frontiers in Immunology, 2022)
Although exo-erythrocytic forms (EEFs) of liver stage malaria parasite in the parasitophorous vacuole (PV) are encountered with robust host innate immunity, EEFs can still survive and successfully complete the infection of hepatocytes, and the underlying mechanism is largely unknown. Here, we showed that sporozoite circumsporozoite protein (CSP) translocated from the parasitophorous vacuole into the hepatocyte cytoplasm significantly mediated the resistance to the killing of EEFs by interferon-gamma (IFN-γ). Attenuation of IFN-γ-mediated killing of EEFs by CSP was dependent on its ability to reduce the levels of autophagy-related genes (ATGs) in hepatocytes. The ATGs downregulation occurred through its enhanced ubiquitination mediated by E3 ligase NEDD4, an enzyme that was upregulated by CSP when it translocated from the cytoplasm into the nucleus of hepatocytes via its nuclear localization signal (NLS) domain. Thus, we have revealed an unrecognized role of CSP in subverting host innate immunity and shed new light for a prophylaxis strategy against liver-stage infection.